Tantangan Ilmu Administrasi Publik: Paradigma Baru Kepemimpinan Aparatur Negara - Johanes Basuki (Public Inspiration : Jurnal Administrasi Publik, 2021)
The greatest challenge of leaders in 21st century is how to be effective leaders. The era of which leaders are expected to make a change with new paradigm in public administration and management, have capability in managing information, productive, and science and technology basis. The new paradigm of leadership of government apparatus is transformational, transactional, resonant, serve public, and have vision. The most important is leader with self-esteem who respects to values for achieving successful and prosperity.